PENERAPAN MEDIA PERMAINAN ULAR NAGA PADA PEMBELAJARAN RUKUN SHOLAT DALAM MENINGKATKAN HASIL BELAJAR SISWA - Aliyasal Sabila; Eni Fariyatul Fahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Particularly at the elementary school level, Islamic Religious Education (PAI) plays a significant role in developing pupils' understanding and character. Because of ineffective teaching strategies and unsuitable learning resources, students frequently struggle to comprehend the pillars of prayer material, which are a set of guidelines and standards. In order to boost second-grade primary school students' interest in learning about the pillars of prayer, this study intends to use the dragon snake game as an engaging and interactive teaching tool. Descriptive qualitative research methodology is employed, and data is gathered through semi-structured interviews, documentation, and participant observation.